Evaluasi Efektivitas Kebijakan K3 Di Lingkungan Kerja Remote: Studi Komparatif Antara Pekerja Kantor Dan Pekerja Dari Rumah - Riris Mega Saputri; Annisa Lulu Zafirah; Agus Halim (CV. SINAR HOWUHOWU, 2026)
This study evaluates the effectiveness of Occupational Safety and Health (OHS) policies in the context of remote work compared to traditional office work. The drastic changes in work systems due to the COVID-19 pandemic have forced organizations to re-examine the role of OHS policies for telecommuting workers. This study uses a comparative approach, using literature review methods and synthesizing relevant secondary data. The results indicate that effective OHS policies in office work environments have not been fully adopted in the remote work context, particularly regarding work ergonomics, psychosocial health risks, and organizational support for remote workers. Furthermore, remote workers exhibit increased musculoskeletal health risks and psychosocial stress when adaptive policies are not in place. This study concludes that OHS policies specifically designed for remote work contexts are necessary and provides practical recommendations for organizations to improve OHS implementation equitably across both work environments. Further research recommendations are directed at empirically measuring OHS policies for remote workers over the long term.